IDENTIFICATION OF SAFETY BARRIERS IN THE PREPARATION AND ADMINISTRATION OF MEDICATIONS BY NURSING PROFESSIONALS - Ana Luísa Petersen Cogo; Fernanda Rosa Indriunas Perdomini; Giovana Ely Flores; Isis Marques Severo; Marise Márcia These Brahm; Mirella de Oliveira Tatsch Dias (Universidade Federal do Paraná, 2024)
Objective: to describe the professional compliance standards regarding knowledge of safety barriers in the preparation and administration of medications. Method: a descriptive, quantitative, retrospective study conducted between January and December 2021 in a hospital in Southern Brazil, involving nursing professionals. The Objective Structured Clinical Examination was implemented in a simulated clinical station using a checklist that included safety barriers. Descriptive analysis was performed using absolute numbers and percentages. Results: a total of 1,682 professionals participated. The safety barriers identified were: electronic medical prescription (86.1%), patient identification wristband (80.3%), pre-filled medication labels before preparation (74.5%), and medication dilution chart (63.9%). Compliance with knowledge of safety barriers was found to be in full compliance for 73.8% of professionals, partially compliant for 19%, and non-compliant for 7.1%. Conclusion: compliance with identified safety barriers demonstrated the professionals' knowledge in care provision.